Play in math learning - Vásquez Yépez, Fernanda Alexandra (2019)
Learning outcomes are increasingly impacted by social interactions. All these theories provide important benefits for math teaching. The Behavioral Theory highlights practice, effort, and feedback in order to increase learning and memory. The Cognitive Theory –associated with comprehension and The Constructivist Theory– considers the ability of children to adapt to and learn from their environment. In the educational field, play is a key tool for optimal learning.